(3jhGbjJ GdehGbjJ (B((3aj eOM GdTF hPeg(B)s - (3YHO Gdedc Hf eMeO Hf ESeGYjd, CHh efUhQ GdKYGdHj,J (B429 (3g` s ((3eMeO Hf jMji Hf YeGQ s)
(3ChdgG (B:s
(3hHYO, CWGd Gddg HbGA ehdGfG GdCejQj GdSjOj GdeGdcj hdj GdfYeI hCOGe YdGg s
(3BNQgG (B:s
(3ajbVj hdG jYO, heG dG jfJLR dG jYO Hg, hgPG ef cdGe fgGjI GdcQGe s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B163s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B187 s
Keywords: (3GdCOHs